2020
DOI: 10.1002/osp4.438
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of a remotely‐delivered behavioural health coaching intervention to limit gestational weight gain

Abstract: Introduction: Gestational weight gain (GWG) and postpartum weight retention (PPWR) are significant, potentially modifiable, contributors to women's future weight and health trajectories. There is a need for feasible and patient-centered (i.e., convenient, remotely-delivered, technology-enhanced, and accessible through the prenatal care setting) behavioural interventions that limit GWG and PPWR. This study tests the feasibility and acceptability of a remotely-delivered behavioural health coaching intervention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 56 publications
1
3
1
3
Order By: Relevance
“…The usability of the Mi Fit app linked to the smartband in our study was evaluated as excellent, as in the RCT Fit4two [ 42 ]. We observed that satisfaction with the messages and midwife support through the app was very high, and the acceptability of the intervention agreed with other RCTs in women who were pregnant and overweight and had obesity, such as SMARTMOMS [ 43 ], txt4two [ 44 ], or studies with women who were pregnant and had any BMI, such as RCT Interact [ 45 ] and the RCTs of Choi et al [ 46 ] and Coughlin et al [ 47 ].…”
Section: Discussionsupporting
confidence: 77%
“…The usability of the Mi Fit app linked to the smartband in our study was evaluated as excellent, as in the RCT Fit4two [ 42 ]. We observed that satisfaction with the messages and midwife support through the app was very high, and the acceptability of the intervention agreed with other RCTs in women who were pregnant and overweight and had obesity, such as SMARTMOMS [ 43 ], txt4two [ 44 ], or studies with women who were pregnant and had any BMI, such as RCT Interact [ 45 ] and the RCTs of Choi et al [ 46 ] and Coughlin et al [ 47 ].…”
Section: Discussionsupporting
confidence: 77%
“…Team-based postpartum care extends outside of the usual clinic setting and can be useful for implementing lifestyle interventions such as postpartum weight management [85]. Involvement of behavioral health coaches for postpartum weight reduction has been found to be feasible and well accepted [86]. In addition, a prior trial showed that an internet-based weight loss program may be feasible and effective in postpartum women of lower income as part of supplement to the WIC program [87].…”
Section: Lifestyle Interventionsmentioning
confidence: 99%
“…Bislang wurden einige Studien, vor allem Pilot-Projekte, auf den Weg gebracht. Ein Wirksamkeitsnachweis Appgestützter Lebensstilinterventionen steht aus, wobei erste Ergebnisse durchaus positiv zu bewerten sind [55,57,60]…”
Section: Digital-gestützte Lebensstilinterventionenunclassified
“…Methoden der Verhaltensänderung lassen sich sehr gut innerhalb von Smartphone-Apps anwenden. Selbstbeobachtung von Gesundheitsdaten in Verbindung mit Zielsetzungen und automatisiertem Feedback werden in einigen der laufenden und geplanten App-gestützten Interventionsstudien integriert 55 56 57 58 . Sogenannte „smarte Sensorik“, darunter Fitnesstracker und Bluetooth-Waagen, sind häufig mit den Apps verknüpft und erleichtern das Aufzeichnen von Gesundheitsdaten, wie Gewicht, Bewegung und Blutdruck.…”
Section: Lebensstilinterventiosstudien In Der Schwangerschaftunclassified
See 1 more Smart Citation